Poly- and perfluorinated substances in environmental water from the Hartbeespoort and Roodeplaat Dams, South Africa - B Batayi; OJ Okonkwo; AP Daso (Water SA, 2021)
Concentrations of poly- and perfluorinated substances (PFASs) were determined in Hartbeespoort and Roodeplaat Dams, South Africa. Water samples were collected from the dams in February–March, and May–June, representing southern hemisphere summer and winter seasons, respectively. Solid phase extraction (SPE) was used to extract the analytes from the water samples and liquid chromatography-tandem mass spectrometry (LC-MS/MS) used for analysis. The mean PFAS concentrations detected ranged from 1.38–346.32 ng∙L-1 and 2.31–262.29 ng∙L-1 in the Hartbeespoort Dam and Roodeplaat Dam, respectively. Perfluorooctanoic acid (PFOA), perfluorooctane sulfonic acid (PFOS), perfluorohexane sulfonic acid (PFHxS) and perfluoroheptanoic acid (PFHpA) were the most dominant PFASs detected. The PFAS concentrations detected were higher in summer than in winter, but the difference between seasons was not statistically significant (p = 1). Furthermore, the concentrations of short-chain PFASs were higher than the longer chains. Overall, the PFAS concentrations in the present study are comparable to those reported in other parts of South Africa, and also Ghana, higher than the concentrations reported in Uganda, Singapore, and Vietnam, and lower than those in Germany, Japan and China. The measured concentrations of PFOA and PFOS raise concerns of human exposure to these chemicals since they are above the USEPA advisory limit. This suggests that communities living within the vicinity of the dams are most likely to be exposed to these chemicals.